Hemoglobin E: a potential interferent in measurement of glycated hemoglobin - Goel, Shobhit; Tripathi, Preeti; Sen, Arijit; Sampath, Sangeetha (International Journal of Advances in Medicine, 2020)
Glycosylated hemoglobin (HbA1C) is a routinely measured parameter to monitor long term glycemic control in patients with diabetes mellitus. There are many potential interferents which can affect measurement of HbA1C by high performance liquid chromatography (HPLC). Variant hemoglobins, especially, are a common source of confusion and errors in HbA1C measurement. Authors present an interesting case of Hb E variant (undiagnosed hitherto) which came to attention when the machine repeatedly failed to give Hb A1C levels. Hb E is the commonest Hb variant in North East India. In the presence of Hb E, HbA1C may not be detected by ion exchange chromatography as both hemoglobin’s co- elute together, thereby causing errors. In such cases, the clinician may resort to subcutaneous sugar monitoring as an alternate or if required, Hb A1C measurement may be done by other techniques like immunoassay technique or boronated affinity chromatography. The laboratory staff and clinicians, both, should be aware of this limitation of HbA1C estimation in patients with HbE and other Hb variants.